A combined cooling and power cogeneration system by coupling duplex free-piston stirling cycles and a linear alternator. (October 2020) - Sun, Yanlei; Luo, Kaiqi; Hu, Jianying; Luo, Ercang; Wu, Zhanghua; Zhang, Limin; Yu, Guoyao; Jia, Zilong; Zhou, Yuan
Abstract: We propose a novel cooling and power cogeneration system based on duplex free-piston thermoacoustic-Stirling cycles and an oscillating linear alternator. In such a cogeneration system, a free-piston Stirling heat engine produces acoustic power via the thermoacoustic power cycle, and a free-piston Stirling refrigerator produces cooling power via the thermoacoustic refrigeration cycle; an oscillating linear alternator is used to couple the free-piston heat engine and refrigerator and simultaneously produces electricity. The configuration and operating principles of the cogeneration system are described along with the thermoacoustic energy transformations and transmission mechanisms. An experimental prototype system was designed, built and successfully operated for the first time. In the preliminary experiments, thermoacoustic oscillation startup typically occurred at heating temperatures around 50 to 60 °C, and a cooling power of about 230 W at -20 °C and an electrical power of more than 6 W were obtained at a heating temperature below 190 °C. The alternator-coupled system has potential applications in heat-driven cogeneration systems for low-grade waste heat recovery and solar energy utilization.